The Role of Job Satisfaction in Developing Job Absorption ( A Case Study of The Faculty of Economics, University of Benghazi) - علي محمد حسين (Dirasat in Economics and Business, 2026)
This study aimed to identify the role of job satisfaction in its dimensions (satisfaction with material and moral incentives, satisfaction with working conditions, satisfaction with promotion opportunities, satisfaction with leadership and supervision style, and satisfaction with work relations) in the development of job absorption at the Faculty of Economics at the University of Benghazi, and the study population consisted of (84) male and female employees, and a questionnaire form was designed as a main tool for collecting field data, and it was distributed to the entire study community, from which (72) questionnaire was retrieved, With a retrieval rate of (86%) and all of them were valid for statistical analysis, This study used the case study methodology, and also used some statistical methods contained in the program of statistical packages for the social sciences (SPSS) in the analysis of data collected in the field, and this study reached several results, the most important of which is the existence of a strong positive correlation with statistical significance between job satisfaction and job absorption, as well as the presence of a strong positive effect of job satisfaction on job absorption in college, and this study recommended several recommendations that are hoped to contribute to improving job satisfaction in the Faculty of Economics University of Benghazi.